Exploring preservice teachers’ experiences of implementing culturally responsive teaching in the ESL classrooms - Idrus, Faizah (Academy Publication, 2023)
Teaching that is culturally responsive (CRT) goes well beyond mentioning students' native cultures or using examples of traditions and customs. This strategy might make students feel included, but it falls short of adding the required rigour to our teaching methods. Although the number of ESL students has increased, teacher preparation programmes sometimes are deprived of preparing incoming teachers to work with a variety of students. The researchers used qualitative methods to investigate how preservice English teachers perceived and engaged with instructional pedagogies that were intended to support their learning and apply to their current practicum experiences and teaching careers in this case study, which was specifically created to improve a pedagogical course on English language development. Data were gathered by observations and interviewing techniques, and they were then inductively examined. According to the results, preservice teachers were most interested in the course material when they were directly related to their prior teaching experiences, and they were least interested when those links were not made clear.